Agrophysical Properties of Irrigated Soils of Sirdarya District (Texas Journal of Agriculture and Biological Sciences, 2023)
The current state of agrophysical properties of irrigated soils of Syrdaryo district is analyzed in the article. In irrigated farming conditions, agrophysical properties of soils are important in increasing soil fertility. According to the obtained data, the mechanical composition of the soil is medium sandy, the amount of physical clay is 46.2% in the driving layer, 36.9% in the sub-driving layer, and its amount changes to 38.2% downwards. The largest part of microaggregates is the amount of large dust fractions (58.4 to 65.8%), especially in the arable layer. The specific gravity (SO) of irrigated gray-meadow soils is 2.63 g/cm3 in the upper part, increasing downwards to 2.65-2.66 g/cm3, bulk density (1.28-1.37 g cm3), total porosity (TP) is 49-51%.